The Effect of Zinc Oxide Nanoparticles on The Expression of Genes Involved in the Production of Pseudomonas Aeruginosa Biofilm Isolated from Cystic Fibrosis Patients - Mona Konkuri; Yousef Erfani; Sharmin Kharrazi; Setareh Haghighat (پیاورد سلامت)
Background and Aim: Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen that is often found in patients with cystic fibrosis, burn wounds, immunodeficiency, and chronic obstructive pulmonary disorder. In addition, P. aeruginosa is also considered one of the most important pathogens causing hospital infections, widely found in medical devices (ventilation), because they tend to grow on moist surfaces. Considering the importance of cystic fibrosis treatment and the ability of P. aeruginosa to form biofilms, this study examines the effect of nano zinc oxide particle on the expression of genes associated in biofilm formation in isolated P. aeruginosa from cystic fibrosis patients. Materials and Methods: Sputum and throat samples from 150 patients with cystic fibrosis were cultured on MacConkey agar culture medium. After an overnight incubation, the grown colonies were determined and confirmed by biochemical tests. An antibiotic sensitivity test by disk diffusion method (Kirby –bauer) were used to determine the antibiotic susceptibility pattern. Zinc nanoparticles were synthesized following established protocols and evaluated using scanning electron microscopy (SEM). The multi-antibiotic-resistant strains were inoculated with 16 µg/ml of 2 nm ZnO nanoparticles and inhibition zone were meseared. The impact of these nanoparticles on the expression levels of gas, retS, lasR, and rhlR genes was assessed using Real-Time PCR. The relative gene expression level was determined using the gene expression method: (ΔΔCt-2). Results: Of the total 150 samples, 73 (48.66%) isolates were identified as P. aeruginosa. All P. aeruginosa isolates were resistant to selected antibiotics. SEM evaluation indicated that the synthesized nanoparticles had an average size of approximately 4 ± 0.44 nm. The results from the Real-Time PCR tests showed a decrease in the expression of the gacA, retS, lasR, and rhlR genes in the presence of the zinc nanoparticles in P. aeruginosa strains. The most significant reduction in gene expression was observed for the rhlR gene, whereas the least reduction was noted for the retS gene. Conclusion: The use of nano zinc oxide can eliminate Pseudomonas aeruginosa infection by preventing biofilm formation and providing better treatment results for cystic fibrosis patients with lung infection.